Islamic Work Ethics in Daily Work Practices: A Case Study of Employees at Bank Syariah Indonesia, Palembang Branch - Harianto Harianto; Heri Junaidi; Melis Melis (UNIVED Press, 2026)
This study aims to explore the practice of Islamic Work Ethics (IWE) in the daily lives of employees of Bank Syariah Indonesia (BSI) Palembang Branch Office after the merger, with a focus on the influence of anxiety related to job placement on the internalization of IWE values. The research method used a qualitative approach with a case study design. Data were collected through in-depth interviews with 15 informants from various banks (former BRI Syariah, BNI Syariah, Mandiri Syariah), observation, and documentation. Data analysis used the Miles & Huberman interactive model. Findings The study found that anxiety about job placement manifests itself in cognitive, affective, behavioral, relational, and spiritual dimensions. Four typologies of employee responses were identified: resilient (strengthened IWE, 20-25%), surviving (stable IWE - decreased OCB, 40-50%), vulnerable (weakened IWE, 20-25%), and problematic (deviant behavior, 5-10%). IWE values ​​such as trustworthiness and honesty are relatively well-maintained, but cross-group collaboration (ukhuwwah) and the meaning of work as worship face significant challenges. This research integrates IWE theory, organizational justice, social identity, and spiritual resilience in the context of Islamic bank mergers in Indonesia.